Integration process and stakeholders' interactions analysis around a protection project: Case of the National park of Gouraya, Algeria (South-western Mediterranean). (1st March 2018) - Boumaour, Amina; Grimes, Samir; Brigand, Louis; Larid, Mohamed
Abstract: Among the most important instruments used for the protection of the Mediterranean marine environment, Marine Protected Areas (MPAs) have demonstrated their efficiency in the preservation of sensitive marine ecosystems and the sustainable management of their resources. In Algeria, only two sites are officially classified as "Specially Protected Area of Mediterranean Importance" and six others are in project, including the extension of the coastal National Park of Gouraya (NPG) to the marine area. This paper addresses the issue of stakeholder involvement in the governance process of high ecological coastal protected areas, highly coveted and exposed to the constraints related to the multiplicity of actors. This study is considered as an Integrated Coastal Zone Management (ICZM) mini-project based on the steps set out in the ICZM Mediterranean Protocol and inspired by the concept founded on ecosystem approach of problems by associating multiple stakeholders around a common project. The management process of the NPG and the involvement of actors were evaluated through direct interviews and a stakeholder analysis using the "MACTOR" method. Results indicate that the current management and the local context are not mature regarding the involvement of the actors. The challenge around issues of sustainable development, especially for civil society, is a relatively new and demanding matter. The human dimension is a top-priority aspect that the sustainable management of the Park and the marine area should be based upon. Highlights: The National Park of Gouraya is subject to intense human pressures owing to its proximity to the city and to the harbour. MPAs constitute a relevant tool to test ICZM processes in order to improve the integration in managing coastal zones. The management process of the Park was evaluated through a stakeholder analysis using the "MACTOR" method. Conflicts of uses, lack of communication and actors' involvement are the main threats to the Park protection process. The human dimension is a top-priority aspect for the sustainable management of the Park and the marine area.